"Damned if you do, damned if you don't": Women's accounts of feigning sexual pleasure. (August 2021) - Stelzl, Monika; Lafrance, Michelle N
Faking orgasm has been identified as a common practice among women and feminist scholars have probed the connections between the socio-cultural meanings associated with faking and heterosex. Expanding on this line of inquiry, feigning sexual pleasure was explored in interviews with 14 women who reported having sex with men. Using a feminist critical discourse analytic approach, we attend to the dilemma that was frequently evoked in women's accounts. Participants explained that feigning sexual pleasure was done in order to protect their partners' ego. However, participants also talked about faking orgasm as being problematic in the sense that it was "deceitful" and "dishonest". These contrasting discursive patterns created a dilemma whereby faking was situated as "necessary" but "dishonest". As a way of negotiating this dilemma, participants made a distinction between exaggerating sexual pleasure and faking orgasm. We posit that exaggeration can be interpreted as a form of material (during the sexual encounter) and discursive (during accounting of the encounter) disruption of dominant discourses of heterosex such as the orgasmic imperative. Drawing on Annamarie Jagose's and Hannah Frith's problematizations of the prevailing tendency to position orgasm as either "authentic" or "fake", we discuss women's negotiation of the limited constructions of "real" pleasure.